Comparison of PD-L1 expression in head and neck squamous cell carcinoma among preoperative biopsy, surgical resection and metastatic lymph node - Sohn, Heeseung; Kim, Meejeong; Kim, Sang-Yeon; Sun, Dong-Il; Lee, Youn Soo (Frontiers in Oncology, 2025)
BackgroundThe interpretation of PD-L1 expression in advanced head and neck squamous cell carcinoma (HNSCC) has recently emerged as a component of companion diagnostics, essential in identifying candidates for immune checkpoint inhibitors (ICIs). However, evaluating PD-L1 expression using the combined positive score (CPS) and tumor proportion score (TPS) has posed challenges, particularly in selecting appropriate specimens and determining hotspots for measurement.MethodsThis study included 68 HNSCC cases from the oropharynx and tongue, collecting complete sets of preoperative biopsy, surgical resection, and metastatic lymph node samples. PD-L1 22C3 staining was performed on each 204 samples to assess PD-L1 expression. The CPS and TPS were measured in all samples using QuPath, an open-source bioimage analysis tool. Statistical comparisons of CPS and TPS among the three specimen types were conducted using Kruskal-Wallis test.ResultsSignificant discrepancies were observed in both CPS and TPS between biopsy and surgical resection (p <0.01, respectively), as well as in both CPS and TPS between resection and metastatic lymph node (p <0.01, respectively). However, no significant statistical differences were observed between the biopsy and metastatic lymph node.ConclusionsOur analysis highlights the heterogeneity of PD-L1 expression across different specimen types. Significant variability exists between the preoperative biopsy and surgical resection, and between surgical resection and metastatic lymph node in patients with HNSCC. These findings suggest that PD-L1 expression varies in response to tumor microenvironment across various tumor areas and time frames. Therefore, individualized PD-L1 assessment for each specimen type is crucial for accurately determining eligibility for ICIs.